2017
DOI: 10.1002/app.46108
|View full text |Cite
|
Sign up to set email alerts
|

The use of noncovalently modified carbon nanotubes for preparation of hybrid polymeric composite materials with electrically conductive and lightning resistant properties

Abstract: In this work, approach to use of noncovalently modified carbon nanotubes is given for preparation of functional hybrid polymeric composite materials (HPCM) based on epoxy resin. Conductive glass-fiber plastics with resistivity in transverse and lengthwise direction 9.0Á3 10 2 and 30-50 Ohm cm, respectively, were obtained. The tetrafluoroethylene telomer and fluorocontaining organosilicon copolymer with amino groups were used as modifiers for carbon nanotubes. Thermal, electrical, and mechanical properties of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 35 publications
0
8
0
Order By: Relevance
“…Hence the improvement of the physical properties (with the addition of GNP at 2 wt%) indicated that the effect of crosslink density on the modification of gamma‐ray and microwave adsorption properties of the nanocomposite reached an optimum level at of 2 wt% GNP. The rise of CNTs amount supports an increase in the electrical conductivity with the modification of microwave properties 46–48 …”
Section: Resultsmentioning
confidence: 85%
“…Hence the improvement of the physical properties (with the addition of GNP at 2 wt%) indicated that the effect of crosslink density on the modification of gamma‐ray and microwave adsorption properties of the nanocomposite reached an optimum level at of 2 wt% GNP. The rise of CNTs amount supports an increase in the electrical conductivity with the modification of microwave properties 46–48 …”
Section: Resultsmentioning
confidence: 85%
“…Nowadays, materials with properties of reflectivity and electromagnetic interference (EMI) shielding effectiveness (SE) have attracted intensive attention in aerospace, engineering, and telecommunication areas, all with civil and military applications 1–6 . Carbon nanomaterials such as carbon nanotubes (CNT), carbon nanofibers, graphite nanoplatelets, and carbon black 3,7–12 are good candidates for developing composites that attend the technological challenges and specifications of the market demands in the mentioned areas.…”
Section: Introductionmentioning
confidence: 99%
“…As per Yurkov et al, epoxy modified with functionalized CNT (FCNT‐COOH) showed better resistance against heat and humidity, unmodified epoxy showed 26% to 32% decrement in ultimate strength after boiling, whereas, FCNT‐COOH epoxy composite decreased by 16% to 17%. In his other article, he reported the effect of modifiers used for altering the CNT surface noncovalently, by using organosilicon fluorocontaining modifier he was able to improve the electrical conductivity and resistance against lightning of carbo‐fiber plastic composite . As reported by Maravi et al, mechanical and electrical properties of polyvinyl alcohol film (PVA) were enhanced by reinforcing it with thermally reduced graphene oxide (TRGO).…”
Section: Introductionmentioning
confidence: 90%